Cognitive ergonomic-driven technology: a pathway to improve mental workload, body posture, and work performance of ageing workers in office setting - Abd Rahman, Nurul Izzah; Ismail, Muhammad Nazirul Iszat (Croatian Interdisciplinary Society, 2025)
Ageing may reduce cognitive function, impacting thinking, reasoning, and memory. One of the potential solutions to address this issue is by utilizing Cognitive-Driven Technology (CEDT). The objective of this study is to investigate the impact of cognitive ergonomic-driven technology on the perceived mental workload, working posture, and task performance of ageing workers. Eight ageing workers were instructed to perform two types of tasks (arithmetic and typing) in two segments (i.e., Segment A (baseline) and Segment B (consisting of CEDT interventions). The accuracy and efficiency of tasks from both segments were evaluated. Mental workload measures (NASA-TLX and Heart rate) and body posture were recorded during the task execution. The recordings were utilized in developing the scenario in a design software, which then further analyzed the Rapid Upper Limb Assessment (RULA) score. One of the crucial findings has been achieved, which result of the correlation analysis shows that in segment B, there was a strong and significant negative correlation between the RULA score and task performance score (r = –0,781, p = 0,022). This means that as the RULA score decreases (indicating better working posture), the task performance improves. These findings emphasize CEDT’s role in maintaining good posture for performance.